Highly Diverse Aquatic Microbial Communities Separated by Permafrost in Greenland Show Distinct Features According to Environmental Niches - Bomberg, Malin; Claesson Liljedahl, Lillemor; Lamminmäki, Tiina; Kontula, Anne (Frontiers in Microbiology, 2019)
The Greenland Analogue Project (GAP) study area in the vicinity of Kangarlussuaq, Western Greenland, was sampled for surface deep groundwater in order to determine the composition and estimate the metabolic features of the microbial communities in water bodies separated by permafrost. The sampling sites comprised a freshwater pond, talik lake, deep anoxic groundwater, glacier ice and supraglacial and meltwater river and melting permafrost active layer. The microbial communities were characterized by amplicon sequencing of the bacterial and archaeal 16S rRNA genes and fungal ITS1 spacer. Additionally, bacterial, archaeal and fungal numbers were determined by qPCR and plate counts, and the carbon and nitrogen substrate utilization pattern was determined with Biolog AN plates and metabolic functions were predicted with FAPROTAX. Different sample types were clearly distinguishable from each other based on community composition, microbial numbers, and substrate utilization, forming four groups, 1) pond/lake, 2) deep groundwater, 3) glacial ice, and 4) meltwater. Bacteria were the most abundant microbial domain, ranging from 0.2 – 1.4  107 16S rRNA gene copies mL-1 in pond/lake and meltwater, 0.1 -7.8  106 copies mL-1 in groundwater and less than 104 mL-1 in ice. The archaeal 16S and fungal 5.8S rRNA genes was generally less than 6.0  103 and 1.5  103, respectively. Actinomycetes, Bacteroidetes and Verrucomicrobia dominated in the pond/lake samples, whereas iron reducing Desulfosporosinus sp. dominated the deep anaerobic groundwater. The glacial ice was inhabited by Cyanobacteria, which were mostly Chloroplast-like. The meltwater contained methano- and methylotrophic Proteobacteria, but had also high relative abundances of the nano-sized Parcubacteria. The archaea composed approximately 1% of the 16S rRNA gene pool in the pond/lake samples with nano-sized Woesearchaeota as the dominating taxon, while in the other sample types archaea were almost negligent. Fungi were also most common in the pond/lake communities, were zoospore-forming Chytridiomycetes dominated. Our results show highly diverse microbial communities inhabiting the different cold Greenlandic aqueous environments and show clear segregation of the microbial communities according to habitat, with distinctive dominating metabolic features specifically inhabiting defined environmental niches and a high relative abundance of putatively parasitic or symbiotic nano-sized taxa.